Ṛta, the cosmic order - Khanna, Madhu (D.K. Printworld in association with Indira Gandhi National Centre for the Arts, 2004)
Aus der Einleitung: "The anthology of seminar papers in this volume on the theme Ṛta, Cosmic Order and Chaos is a culmination of an interdisciplinary cross-cultural dialogue initiated by the Indira Gandhi National Centre for the Arts ..."